Media Literacyof High School Students in Critical and Safe Social Media - Tijan, Tijan; Amal Abdillah, Yan; Rachman, Maman; Hardi Saputro , Iwan (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Misconceptions about free speech often led to digital crimes. In Indonesia, cases of defamation and hate speech on social media continue to increase. Especially during this COVID-19 pandemic, where people are doing more online activities. Therefore, students should learn media literacy to not be part of the crimes. In this quasi-experimental research, media literacy material was integrated with Pancasila and citizenship education at the senior high school level in Semarang District. The control group used expository learning with a video conference application such as Zoom and uploaded their assignment to Google Drive. The experimental group used discussion-based learning and posted assignments on their Instagram accounts. In this study, ten multiple-choice questions presented digital contents that were proven to have violated the Electronic Information and Transaction Law. Students should identify the violations committed and choose the correct answer. Both groups showed similar pre-test (6.00 and 5.82) and post-test (6.47 and 6.00) scores. However, the experimental group showed attitudes change in the discussion. Many of them commented, "be careful in commenting" which is the best way to avoid online violation. This study recommends teachers conduct democratic learning through social media to provide students with real experiences and improve their social skills.